Antidepressant-like effects of the Punica granatum and citalopram combination are associated with structural changes in dendritic spines of granule cells in the dentate gyrus of rats - Vega-Rivera, Nelly-Maritza; González-Trujano, María Eva; Luna-Angula, Alexandra; Sánchez-Chapul, Laura; Estrada-Camarena, Erika (Frontiers in Pharmacology, 2023)
Abstract Natural products such as phytoestrogens-enriched foods or supplements have been considered as an alternative therapy to reduce depressive symptoms associated with menopause. It is known that the aqueous extract of Punica granatum (AE-PG) exerts antidepressant-like effects by activating -estrogen receptors and facilitates the antidepressant response of the clinical drug citalopram (CIT). However, the effects on neuroplasticity are unknown. Here, we investigated the antidepressant-like response of combining AE-PG and CIT at sub-optimal doses, analyzing their effects on the formation and maturation of dendrite spines in granule cells as well as on the dendrite complexity. Ovariectomized Wistar rats (3-month-old) were randomly assigned to one of the following groups: A) control (saline solution as vehicle of CIT and AE-PG, B) AE-PG at a sub-threshold dose (vehicle of CIT plus AE-PG at 0.125 mg/kg), C) CIT at a sub-threshold dose (0.77 mg/kg plus vehicle of AE-PG), and D) a combination of CIT plus AE-PG (0.125 mg/kg and 0.77 mg/kg, respectively). All rats were treated intraperitoneally for 14 days. Antidepressant-like effects were evaluated using the forced-swimming test (FST). The complexity of dendrites and the number and morphology of dendrite spines of neurons were assessed in the dentate gyrus after Golgi-Cox impregnation. The expressions of the mature brain-derived neurotrophic factor (mBDNF) in plasma and of mBDNF and synaptophysin in the hippocampus, as markers of synaptogenesis, were also determined. Administration of CIT combined with AE-PG, but not alone, induced a significant antidepressant-like effect in the FST with an increase in the dendritic complexity and the number of dendritic spines in the dentate gyrus (DG) of the hippocampus, revealed by the thin and stubby categories of neurons at the granular cell layer. At the same time, an increase of mBDNF and synaptophysin expression was observed in the hippocampus of rats that received the combination of AE-PG and CIT.